2013
DOI: 10.2337/dc12-1112
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Stress- and Food Cue–Induced Food Craving in Obesity

Abstract: OBJECTIVEObesity is associated with alterations in corticolimbic-striatal brain regions involved in food motivation and reward. Stress and the presence of food cues may each motivate eating and engage corticolimibic-striatal neurocircuitry. It is unknown how these factors interact to influence brain responses and whether these interactions are influenced by obesity, insulin levels, and insulin sensitivity. We hypothesized that obese individuals would show greater responses in corticolimbic-striatal neurocircui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
155
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(168 citation statements)
references
References 50 publications
10
155
2
1
Order By: Relevance
“…Whereas some prior studies have found a significant MRI signal change in the hypothalamus to food vs. nonfood cues (13,(43)(44)(45), others have not (46)(47)(48). Inconsistent findings could be due to variations in study design, differences in participant characteristics, and/or variations in image acquisition, which may be important in the hypothalamus, a small region that is affected by signal loss due to magnetic susceptibility artifacts in blood oxygen level-dependent (BOLD) imaging.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas some prior studies have found a significant MRI signal change in the hypothalamus to food vs. nonfood cues (13,(43)(44)(45), others have not (46)(47)(48). Inconsistent findings could be due to variations in study design, differences in participant characteristics, and/or variations in image acquisition, which may be important in the hypothalamus, a small region that is affected by signal loss due to magnetic susceptibility artifacts in blood oxygen level-dependent (BOLD) imaging.…”
Section: Discussionmentioning
confidence: 96%
“…In response to this, new databases of food images (of standardised luminosity, complexity and known calorie content) are becoming available with the hope of facilitating comparability across appetite neuroimaging studies (25). Conversely, some modern experimental paradigms have tried to account for the heterogeneity in personal food-cue reactivity by tailoring the stimuli used to elicit appetitive neuronal responses to pre-assessed personal preferences (26).…”
Section: A Word About Reproducibilitymentioning
confidence: 99%
“…been used previously to elicit anxiety, food craving, and relaxation through the vivid remembrance of stressful, craving-related, and neutral/relaxing scenarios (Hommer et al, 2013;Jastreboff et al, 2013;Seo et al, 2014). Two scripts each were developed for stress, favorite-food, and neutral/relaxing conditions using the Scene Development Questionnaire (Sinha, 2013) and audiotaped in a female voice for presentation in the scanner.…”
Section: Methodsmentioning
confidence: 99%
“…The guided-imagery fMRI procedure, in which personal experiences are recalled and developed into scripts to be recorded and played back in the scanner, is validated and has been used in both adults and adolescents (Hommer et al, 2013;Jastreboff et al, 2013;Sinha, 2013). To our knowledge, this is the first study to investigate the relationship between childhood trauma and the neural correlates of personally salient appetitive, aversive, and neutral/relaxing cues.…”
Section: Introductionmentioning
confidence: 99%